PEMANFAATAN MEDIA BLOGGER DALAM PEMBELAJARAN MENULIS CERPEN MENGGUNAKAN MODEL DISCOVERY LEARNING PADA SISWA KELAS X SMKN 02 BALEENDAH - Sary Sukawati; Shopia Trilaksono; Aditya Permana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
One type of text that must be mastered in learning Indonesian is short stories. The problem that still often occurs in writing activities is that short stories are still considered difficult by students. This is due to several factors such as the lack of idea acquisition, and learning which is still monotonous due to the lack of use of supporting media. Media Blogger is the solution offered. The use of the internet and the practical use of media are felt to make learning to write short stories more interesting. In its implementation, researchers used the discovery learning model. The aim of this research is to find out the usefulness of using Blogger as a medium in learning to write short stories. The research method used is descriptive qualitative. The research was carried out offline with a sample of class X students at SMKN 2 Baleendah. Data collection was carried out using observation techniques and student questionnaires. The observation results show that 90% of the learning activities have been carried out properly according to the discovery learning syntax. The results of the questionnaire show that the use of Blogger media is in the very good category. 95% of students stated that Blogger media was useful in learning to write short stories, although students still experienced some obstacles, especially on gadgets or laptops